Nanoporous Amorphous Carbon with Exceptional Ultra-High Strength - Castillo Castro, Daniel (2023)
Nanoporous materials show a promising combination of mechanical properties in terms of their relative density; while there are numerous studies based on metallic nanoporous materials, here we focus on amorphous carbon with a bicontinuous nanoporous structure as an alternative to control the mechanical properties for the function of filament composition.Using atomistic simulations, we study the mechanical response of nanoporous amorphous carbon with 50% porosity, with sp (Formula presented.) content ranging from 10% to 50%. Our results show an unusually high strength between 10 and 20 GPa as a function of the (Formula presented.) content. We present an analytical analysis derived from the Gibson–Ashby model for porous solids, and from the He and Thorpe theory for covalent solids to describe Young’s modulus and yield strength scaling laws extremely well, revealing also that the high strength is mainly due to the presence of sp (Formula presented.) bonding. Alternatively, we also find two distinct fracture modes: for low (Formula presented.) samples, we observe a ductile-type behavior, while high (Formula presented.) leads to brittle-type behavior due to high high shear strain clusters driving the carbon bond breaking that finally promotes the filament fracture. All in all, nanoporous amorphous carbon with bicontinuous structure is presented as a lightweight material with a tunable elasto-plastic response in terms of porosity and sp (Formula presented.) bonding, resulting in a material with a broad range of possible combinations of mechanical properties.